Feminization of the Police from the Perspective of Comprehensive Risk Minimization - Magiera, Maciej (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
Nowadays, the Police have a significant impact on the security and public order in Poland having actually become a litmus test of how the authorities approach the general public. Furthermore, Polish society is developing the characteristics of risk society and information society, which stimulates a special interest of citizens and the mass media in all the activities of uniformed institutions. Their attitude to current political events is often assessed and their effectiveness criticized. Therefore, the impact of contemporary modernization processes on the Police, including feminization, is a worthwhile task. For this purpose, extremely useful have been research methods, such as case studies, comparative analysis and system analysis.

Współcześnie Policja istotnie wpływa na bezpieczeństwo i porządek publiczny w III RP, stała się wręcz papierkiem lakmusowym podejścia władzy do ogółu. Dodatkowo społeczeństwo polskie nabywa cech społeczeństwa ryzyka i społeczeństwa informacyjnego, co kreuje szczególne zainteresowanie obywateli i mass mediów wszelką działalnością instytucji mundurowych. Często ocenia się ich stosunek do aktualnych wydarzeń politycznych, a także poddaje krytyce skuteczność. Warto zatem przeanalizować jaki wpływ na Policję wywierają współczesne procesy modernizacyjne – jednym z nich jest feminizacja. W tym celu niezwykle przydatne okazały się metody badawcze, jak studium przypadku, analiza porównawcza czy analiza systemowa.
Feminizacja policji z perspektywy kompleksowego minimalizowania ryzyk
Keywords: feminization; Police; public safety; risk society; uniformed services; risk minimization; feminizacja; Policja; bezpieczeństwo publiczne; społeczeństwo ryzyka; służby mundurowe; minimalizowanie ryzyka